Association of candidate genes with heading date in a diverse Dactylis glomerata population. (December 2017) - Zhao, Xinxin; Bushman, B. Shaun; Zhang, Xinquan; Robbins, Matthew D.; Larson, Steven R.; Robins, Joseph G.; Thomas, Aaron
Highlights: The CO1, FT1, VRN-like MADS, and PPD1-like genes were amplified and sequenced in a diverse orchardgrass population that included cultivars and collections from around the world. The entries exhibited high allelic variation and little LD among loci indicative of perennial self-incompatible grasses. Equal-dose association modelling identified several significant polymorhpisms within the DgCO1 and DgFT1 genes. By modelling allele dosage for a tetraploid, additional loci were detected in the DgCO1, DgMADS, and DgPPD1-like genes. Abstract: Flowering occurs in response to cues from both temperature and photoperiod elicitors in cool-season, long-day forage grasses, and genes involved in sensing the elicitors and inducing downstream flowering responses have been associated with heading date and flowering time in perennial forage grasses as well as cereal grasses. In this study we test for association between orchardgrass ( Dactylis glomerata L.) heading date and polymorphisms in the CONSTANS ( DgCO1 ), FLOWERING TIME ( DgFT1 ), a VRN1 like MADS-box ( DgMADS ), and PHOTOPERIOD ( DgPPD1-like ) containing genes. A diverse population of 150 genotypes was measured for heading date across three years, genotyped, and candidate genes sequenced. Although pairwise population kinship values were generally low, the genotypes fit into a two-group structure model. Linkage disequilibrium decayed rapidly, reaching r 2 levels below 0.2 within the 500 bp of each gene. SNPs significantly associated with heading date were detected in equal-dose and tetraploid dosage models. The DgCO1 gene had the most significant polymorphisms and those with the largest effects, while DgMADS had several significant polymorphisms in its first intron with smaller effects. These polymorphisms can be used for further validation, selection, and development of breeding lines of orchardgrass.